Strong ellipticity and spectral properties of chiral bag boundary conditions - Beneventano, Carlota Gabriela (2003)
We prove strong ellipticity of chiral bag boundary conditions on even dimensional manifolds. From a knowledge of the heat kernel in an infinite cylinder, some basic properties of the zeta function are analysed on cylindrical product manifolds of arbitrary even dimension.